2004
DOI: 10.1111/j.1464-5491.2004.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone improves insulin sensitivity, glucose tolerance and ambulatory blood pressure in subjects with impaired glucose tolerance

Abstract: Consistent with its effects in patients with Type 2 diabetes, rosiglitazone substantially improved whole body insulin sensitivity and the glycaemic and insulinaemic responses to an OGTT and meal tolerance test in subjects with persistent IGT. Furthermore, rosiglitazone reduced systolic and diastolic ambulatory blood pressure in these subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 35 publications
5
49
0
Order By: Relevance
“…[12][13][14][15][16] RSG has been shown to reduce oxidative stress, thus ameliorating endothelial dysfunction and improving blood vessel elasticity. 31 However, no study to date has examined the effects of RSG on the RAS in human adipocytes and obesity-associated hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16] RSG has been shown to reduce oxidative stress, thus ameliorating endothelial dysfunction and improving blood vessel elasticity. 31 However, no study to date has examined the effects of RSG on the RAS in human adipocytes and obesity-associated hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…We then proceeded to determine the effect of TNF-␣ on AGT protein expression and Ang II secretion, to elucidate a potential pathway for insulin leading to obesity-associated hypertension through its effects on adipose tissue. Lastly, because the insulin sensitizer rosiglitazone (RSG) has been shown to lower blood pressure in animal models, patients with impaired glucose tolerance, patients with type 2 diabetes mellitus, and nondiabetic hypertensive individuals, [12][13][14][15][16] we investigated the effect of RSG on AGT expression and Ang II secretion in human adipocytes.…”
mentioning
confidence: 99%
“…While rosiglitazone and metformin are typically used in the treatment of type 2 diabetes, recent studies have demonstrated that both metformin (24) and the thiazolidinediones troglitazone (49) and rosiglitazone (50) are capable of reducing the rate of conversion from impaired glucose tolerance to diabetes. Whether reduced islet amyloid formation is a basis for these effects is an interesting and important question.…”
Section: Fig 4 Amentioning
confidence: 99%
“…The overall risk that patients with IGT will develop diabetes is 3-9% per year in the United States (Ipp 2000). TZDs improve insulin sensitivity in a range of insulin-resistant states without diabetes, including obesity and IGT (Ghanim et al 2001;Sekino et al 2003;Bennett et al 2004).…”
Section: Use In Diabetes Preventionmentioning
confidence: 99%